Low-temperature scanning tunneling microscopy and spectroscopy of noble-metal surfaces - Zupanič, Erik (Array, 2009)
Summary: Low-index surfaces of copper single crystals were studied by scanning tunneling microscopy (STM) and spectroscopy (STS). The experiments were performed under ultra-high vacuum conditions at room- and close to liquid helium- temperatures. At lower temperatures thermal drifts are largely reduced, a better STM mechanical stability is achieved and improved spectroscopy measurements, with the energy resolution shifted from meV to μeV, are possible. Low-index surfaces of bulk copper single crystals are unstable at room temperature and show poor atomic resolution with unstable single-atomic steps. In order to reduce thermal vibrations and improve atomic resolution, such surfaces must be cooled close to liquid helium temperature. At cryogenic temperatures individual surface defects, adsorbents and electronic standing waves can be studied. In addition, individual adatoms can be manipulated by STM into desired nanostructures and analyzed by STS. By measuring dI/dU(U), which is proportional to the local density of states, spectroscopic information with high spatial resolution can be obtained